Influence of Urban Microclimate on Air-Conditioning Energy Needs and Indoor Thermal Comfort in Houses - Feng-Chi Liao; Ming-Jen Cheng; Ruey-Lung Hwang (Advances in Meteorology)
A long-term climate measurement was implemented in the third largest city of Taiwan, for the check of accuracy of morphing approach on generating the hourly data of urban local climate. Based on observed and morphed meteorological data, building energy simulation software EnergyPlus was used to simulate the cooling energy consumption of an air-conditioned typical flat and the thermal comfort level of a naturally ventilated typical flat. The simulated results were used to quantitatively discuss the effect of urban microclimate on the energy consumption as well as thermal comfort of residential buildings. The findings of this study can serve as a reference for city planning and energy management divisions to study urban sustainability strategies in the future.